The use of FM dyes to analyze plant endocytosis - Malínská, Kateřina; Jelínková, Adriana; Petrášek, Jan (Methods in molecular biology (Clifton, N.J.), 2014)
FM (Fei-Mao) styryl dyes are compounds of amphiphilic character that are used for the fluorescence tracking of endocytosis and related processes, i.e., the internalization of membrane vesicles from the plasma membrane (PM) and dynamics of endomembranes. Staining with FM dyes and subsequent microscopical observations could be performed both on the tissue and cellular level. Here, we describe simple procedures for the effective FM dye staining and de-staining in root epidermal cells of Arabidopsis thaliana seedlings and suspension-cultured tobacco cells. The progression of FM dye uptake, reflected by an increased amount of the dye in the endosomal compartments, is monitored under the fluorescence microscope in a time-lapse manner. The data obtained can be used for the characterization of the rate of endocytosis and the function of components of endosomal recycling machinery.
Keywords: endocytóza; Microscopy, Fluorescence; molekulární biologie; Phenylurea Compounds; fenylmočovinové sloučeniny; Arabidopsis; fluorescenční mikroskopie; fluorescenční barviva; buněčný tracking; Fluorescent Dyes; kořeny rostlin; Molecular Biology; Plant Roots; Endocytosis; Staining and Labeling; Cell Tracking; barvení a značení